2023
DOI: 10.3329/bjms.v22i2.64993
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for emergencies and disasters, and health competencies among people with epilepsy

Abstract: Objective: Epilepsy, one of the chronic diseases with a substantial share in the global burden of disease, can be brought under control with proper disease management. A part of disease management is preparedness for emergencies and disasters. Health competence is a protective mechanism in developing behavior and readiness for emergencies and disasters. This study aims to determine the relationship between preparedness against emergencies and disasters and health literacy competencies in people with epilepsy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Moreover, the results of the study conducted by Shibahara et al [11] indicated an increase in epileptic patients after the Great East Japan Earthquake. Additionally, Yilmazel [12] conducted a study during April-May 2022, targeting 270 epileptic patients, aged 18 and above, residing in the Central Black Sea region of Turkey, to clarify the relationship between disaster preparedness and health literacy.…”
Section: Introduction Research Backgroundmentioning
confidence: 99%
“…Moreover, the results of the study conducted by Shibahara et al [11] indicated an increase in epileptic patients after the Great East Japan Earthquake. Additionally, Yilmazel [12] conducted a study during April-May 2022, targeting 270 epileptic patients, aged 18 and above, residing in the Central Black Sea region of Turkey, to clarify the relationship between disaster preparedness and health literacy.…”
Section: Introduction Research Backgroundmentioning
confidence: 99%